Ethik – wozu und wie weiter? - Hetzel, Andreas; Gamm, Gerhard (transcript, 2015)
What do we mean when we speak of ethical requirements or judgments? What is the task of philosophical ethics in public debates? How can the moral point of view orient us regarding competing economic, political, and legal demands? Today, philosophical ethics is under great pressure to become more scientific, and mostly specializes in working out specific follow-up costs of the mechanization of human life. But there is less and less clarity on how it should define itself and its task in the first place. Against this background, the contributions to this volume ask about the intrinsic purpose of the ethical.